Kajian Eksistensi Bangunan Cagar Budaya Di Jl. Dr. Cipto Kota Semarang - Rubiantoro, Eko Anton (Jurnal Riptek, 2024)
The city of Semarang is rich in a multitude of cultural heritage. In accordance with the Decree of the Mayor of the Regional Head of Level II Semarang No. 646/50/TAHUN/1992 concerning Building Conservation, Ancient/Historic Buildings in the Semarang Level II Regional Municipality Area, several Cultural Heritage Buildings have been designated. The types of buildings determined consist of socio-cultural buildings, religious buildings and business buildings. Jl. Dr. Cipto was the development of the Dutch city area after the Old City was full so that Dutch and Chinese people living in Semarang began to occupy this area along with the emergence of supporting buildings. Research related to the existence of cultural heritage buildings cannot be separated from the role of trusted sources who understand or understand the object being studied. This research aims to obtain comprehensive facts, data and information related to the existence of Cultural Heritage Buildings which are the object of research. The primary survey in this research was carried out to obtain primary data or information, namely data or information obtained directly from the field. Field survey with an argumentative and persuasive approach to dig up information to strengthen institutional data and complement existing data. The technique for obtaining this data is observation, measurement and interviews. Apart from that, the survey was carried out using literature studies, reports related to previous Cultural Heritage Building data. The analysis results show that the Cultural Heritage Building on Jalan Dr. Most of this Cipto has strong characteristics of modern architecture, a style that was popular at the beginning of the 20th century. Some of the buildings are not multi-storey, and there are parts of the core building that resemble multi-storey towers. The building orientation tends to be west. The foundation of a building made of stone that supports the main structure. Until now, the building still looks sturdy and well maintained. The existence of cultural heritage buildings in the Old City area, especially on Jl. Dr. Cipto Semarang has an important meaning in supporting the existence of the region from its inception until today. The existence of a cultural heritage building on Jl. Dr. Cipto demonstrated the consistency of function and transformation of the building's function according to the needs of the time but did not change the shape/facade of the existing building. The role of building managers needs to continue to be improved by increasing cooperation between the Government, Building Management Organizations, Building Owners and Investors. The Semarang City Government needs to continue to play an active role in efforts to maintain the existence of cultural heritage buildings in the Jl. Dr. Cipto is mainly related to policies to support the existence of cultural heritage buildings so that they continue to exist.